THE IMPLEMENTATION OF TEACHING SPEAKING PROGRAM AT LANGUAGE CENTER ENGLISH COURSE PARE KEDIRI - Nurohman, Eko (Jurnal Pendidikan Bahasa Inggris Proficiency, 2020)
Non – formal education is one of the solution to help the student learning the subject.One of non – formal education is English course to complete the studying in formal education, to give more knowledge, human skill, and to be able to develop the ability, improving the skill and independence. When the students cannot get maximal in speaking English at school, they can join some courses that is focusing on English. LANGUAGE CENTER English Course has known well to make students able to speak English because they will be helped by 100 teachers who is professional in English. The Implemntation of teaching speaking program at LANGUAGE CENTER English Course are including teacher’s preparation, material taught, teachers’ evaluation in learning, and students’ response toward the teacher in teaching speaking .The research used descriptive qualitative as research design. The subject was 13 students of basic speaking class at LANGUAGE CENTER English Course. The method used in collecting data was interview, observation and documentation. Interview and observation were used for collecting data on teacher’s preparation, material taught, teachers’ evaluation in learning, and students’ response toward the teacher in teaching speaking at LANGUAGE CENTER English Course and documentation used for collecting picture and video that we did research. The result of research is to show that teacher’s preparation, material taught, teacher’s evaluation and students’ response in teaching speaking program at LANGUAGE CENTER English Course was very good.